Penerapan Model Pembelajaran Kooperatif Tipe Make A Match untuk Meningkatkan Prestasi Belajar Matematika Siswa SD - Mardiana Mardiana (Jurnal Akademik Pendidikan Matematika, 2022)
The problem formulation in this study is: (1) How to apply the Make A Match cooperative learning model to improve math learning achievement “Mathematics Measurement Materials” in students Class VI Elementary School 45 Buton ? (2) How to improve achievement of learning “Mathematics Measurement Materials” using cooperative learning model type Make A Match in students Class VI Elementary School 45 Buton ?". In accordance with the type of research chosen, namely action research, this study uses a research model from Kemmis and Taggart that is in the form of a spiral from one cycle to the next. Each cycle includes planning, action, observation, and reflection.The next step in the next cycle is revised planning, action, observation and reflection. Before entering cycle I, a preliminary action is carried out in the form of problem identification. From the results of the research conducted obtained the results that the completion of learning cycle I (54%), cycle II (74%) and cycle III (94%). The conclusion in this study is (1) The application of cooperative learning model type Make A Match can improve achievement of learning “Mathematics Measurement Material” In students. Improved achievement of learning “Mathematics Measurement Materials” using cooperative learning model type Make A Match in students Class VI Elementary School 45 Buton ? cycle I (54%), cycle II (74%) and cycle III (94%).